Local Shops of Cantanhede Online Platform - Teixeira, M. (Open Schools Journal for Open Science, 2020)
This project is an initiative of a group of students of the technical course in management and programming of computer systems, taught at the Technical School of Cantanhede, which will allow consumers, through the Internet, to discover micro and small companies of the city through web pages. The idea came about following the analysis that has been made to the increasing decline of traditional shops and markets because of the increasing of large shopping centers. The project's objectives are to promote trade and proximity services; counteract the trend of exclusive promotion of large commercial groups to digital platforms; and give visibility to small local shops, so that they are able to attract new customers. It should be noted that this project aims to be multidisciplinary and promote a culture of proximity between the local community and the school community, benefiting responsible citizenship.